Review of Metronidazole Dosing in Preterm Neonates - Dannelley, Jennifer F.; Martin, Erin M.; Chaaban, Hala; Miller, Jamie L. (American Journal of Perinatology, 2017)
Metronidazole dosing recommendations vary significantly for premature infants in pediatric dosing references and can result in confusion for prescribers. We performed a literature search identifying articles evaluating the pharmacokinetics and dosing of metronidazole in premature infants. The search was limited to English-language articles in MEDLINE (January 1946 to December 2016), EMBASE (January 1974 to December 2016), and International Pharmaceutical Abstracts (January 1970 to December 2016). Reference citations from relevant articles were also reviewed. Six pharmacokinetic studies, representing 152 neonates, were included; however, only three of the well-defined studies were reviewed in depth, and the other three studies were considered foundational. The pharmacokinetic studies included in this review indicate that some published dosing recommendations in pediatric dosing references may result in subtherapeutic metronidazole concentrations. Therefore, postmenstrual age based dosing recommendations were provided by the authors of these pharmacokinetic studies based on a pharmacodynamic target of 6 to 8 mg/L; yet, these dosing recommendations differ from one another. The pharmacokinetic studies included in this review provide some guidance to dosing; however, a major limitation is that outcomes of clinical efficacy and safety were not evaluated. Future studies targeting the optimal dosing and serum concentrations required for clinical efficacy are needed.
Keywords: metronidazole; neonate; pharmacokinetics